2019
DOI: 10.1186/s41936-019-0114-2
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Histopathological studies on female and male Wistar rats fed on genetically modified soybean meals (Roundup Ready)

Abstract: Background: Roundup Ready became the most cultivated genetically modified (GM) crop in the world. The aim of this study was to evaluate the effects of a diet containing GM soybean meal (RUR) on male and female Wistar rats. The body weights, food consumption, hematology, serum biochemistry, organ weight, and histopathological examination were compared between rats fed on GM soybean and those fed non-GM soybean after consumption of test diets for 18 weeks. Methods: Sixty weaned Wistar albino rats (30 females and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
2
6
1
Order By: Relevance
“…The present study showed significantly higher serum insulin and glucose levels in the HFD group compared to the control group. The present results coincide with several researchers who confirmed that oxidative stress and inflammation are the major components responsible for the pathogenesis of insulin resistance (IR) [ 45 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed significantly higher serum insulin and glucose levels in the HFD group compared to the control group. The present results coincide with several researchers who confirmed that oxidative stress and inflammation are the major components responsible for the pathogenesis of insulin resistance (IR) [ 45 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the group of male rats administered with "Activegel" at a dose of 500 mg/kg we registered a signi cantly lower hemoglobin concentration (4.8%) and higher glucose concentration (31.6%) compared with the control. One should note that the above changes in the indices of general and biochemical blood analysis of of rats, although different from the control group, remained within normal range [19,21,23,24].…”
Section: Resultsmentioning
confidence: 73%
“…In the group of female rats injected with the test substance at a dose of 500 mg/kg a signi cantly lower glucose concentration and higher concentration of inorganic phosphorus (46.7%) was observed compared with the control. It is important to note that these altered biochemical parameters, according to the literature, were within normal range [21,24]. Thus, the in vivo toxicity of the new generation hydrophilic gel was evaluated using generally accepted approaches to clinical trials of the compounds and it was shown that this substance, according to the classi cation of the Environmental Protection Agency can be classi ed as hazard category IV, is not toxic.…”
Section: Resultsmentioning
confidence: 99%
“…In the group of male rats administered with “Activegel” at a dose of 500 mg/kg we registered a significantly lower hemoglobin concentration (4.8%) and higher glucose concentration (31.6%) compared with the control. One should note that the above changes in the indices of general and biochemical blood analysis of of rats, although different from the control group, remained within normal range [ 19 , 20 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the group of female rats injected with the test substance at a dose of 500 mg/kg a significantly lower glucose concentration and higher concentration of inorganic phosphorus (46.7%) was observed compared with the control. It is important to note that these altered biochemical parameters, according to the literature, were within normal range [ 20 , 23 ].…”
Section: Resultsmentioning
confidence: 99%